Systematic review of diagnostic pathways for patients presenting with acute abdominal pain. (13th April 2018) - de Burlet, Kirsten J; Ing, Andrew J; Larsen, Peter D; Dennett, Elizabeth R
Abstract: Purpose: Abdominal pain is the most common reason for surgical referral. Imaging, aids early diagnosis and treatment. However unnecessary requests are associated with increased costs, radiation exposure and increased length of stay. Pathways can improve the quality of the diagnostic process. The aim of this systematic review was to identify the current evidence for diagnostic pathways and their use of imaging and effect on final outcomes. Data sources: A systematic search of Embase, Medline and Cochrane databases was performed using keywords and MeSH terms for abdominal pain. Study selection: All papers describing a pathway and published between January 2000 and January 2017 were included. Data extraction: Data was obtained about the use of imaging, complications and length of stay. Quality assessment was performed using MINORS and Level of Evidence. Results: Ten articles were included, each describing a different pathway. Five studies based the pathway on literature reviews alone and five studies on the results of their prospective study. Of the latter five studies, four showed that routine imaging increased diagnostic accuracy, but without showing a reduction in length of stay, complication rate or mortality. None of the studies included evaluated use of hospital resources or costs. Conclusion: Pathways incorporating routine imaging will improve early diagnosis, but has not been proven to reduce complication rates or hospital length of stay. On the basis of this systematic review conclusions can therefore not be drawn about the pathways described and their benefit to the diagnostic process for patients presenting with abdominal pain.